Diagnóstico pré-natal de malformação fetal: um olhar sobre o casal - Maria Eugenia da Costa Machado (2010)
A qualitative descriptive study was performed to investigate major marital repercussions resulted from a fetal malformation diagnosis during antenatal. To this end, we interviewed ten couples whose fetuses had some malformation. All of them were in prenatal care at the Center for Fetal Medicine, Hospital of the Universidade Federal de Minas Gerais (CEMEFE HC / UFMG). Semi-structured interviews were conducted individually in a single meeting with each woman and each partner separately. All interviews were conducted by the same investigator and were fully recorded. A thematic analysis of the interviews was performed. Through this process, three categories of analysis were observed: experience of couples facing the diagnosis of fetal malformation, marital relationship aspects influenced by the diagnosis of fetal malformation and factors that interfere handling the diagnosis of fetal malformation. These categories were described and discussed from the literature found. Malformation seems to produce a moment of crisis, but not a common crisis because couples have to use resources beyond habitual ones used in common crisis. It was noticed that couples facing these diagnosis experience intense and variables feelings and emotions, with wild swings, which can trigger the isolation or the approach of the couple, as well as worsening or improvement in the relationship, regardless of diagnosis and fetal prognosis. The guilt experience has been revealed as the main finding of the research that interferes directly and decisively in the marital relationship, with both men and women. In short, we could see that marital relationship influences on challenging the diagnosis of fetal malformation, and is influenced by the same news. The results of this research prove literature data which is necessary psychologist support to these couples, resulting in a better way of lived reality.